Low‐dose aspirin treatment improves endometrial receptivity in the midluteal phase in unexplained recurrent implantation failure. Issue 2 (23rd April 2021) - Zhang, Xiaoxin; Guo, Feng; Wang, Qiaohong; Bai, Wenxin; Zhao, Aimin
Abstract: Objective: To compare endometrial receptivity in patients with and without unexplained recurrent implantation failure (URIF) and the benefits of low‐dose aspirin treatment in women with URIF. Methods: A retrospective study was conducted at Ren Ji Hospital, Shanghai, from January 2014 to January 2017. Endometrial thickness, pulsatility index (PI), resistive index (RI), and systolic‐to‐diastolic ratio (S/D) values of endometrial and uterine perfusion were recorded and compared between women with and without URIF. Receiver operating characteristic (ROC) curve analysis was used to evaluate the predictive accuracy of the risk of URIF. Ultrasonography examination was repeated after 2 months of treatment with low‐dose aspirin. Results: PI, RI, and S/D values for endometrial blood flow were significantly higher in URIF patients than the control group ( P  < 0.001). The predictive indexes were 0.833, 0.857, and 0.839, respectively. Differences between the groups for endometrial thickness and impedance of uterine perfusion were not significant ( P  > 0.05). After low‐dose aspirin treatment, endometrial and uterine arterial blood flow resistance in URIF patients was significantly lower than before treatment ( P  < 0.05). Conclusion: URIF patients had inappropriate endometrial blood flow. Doppler parameters are promising for predicting women at high risk of URIF. Low‐dose aspirin treatment can improve endometrial receptivity. Abstract : Doppler parameters are promising for predicting women at high risk of unexplained recurrent implantation failure. Low‐dose aspirin treatment can improve endometrial receptivity.